Mean Corpuscular Volume Is Correlated with Liver Fibrosis Defined by Noninvasive Blood Biochemical Indices in Individuals with Metabolic Disorders Aged 60 Years or Older - Kaneko, Yousuke; Kawano, Yutaka; Kawata, Saki; Mori, Kensuke; Hosoki, Minae; Hori, Taiki; Miyataka, Kohsuke; Tsuji, Seijiro; Hara, Tomoyo; Yamagami, Hiroki; Otoda, Toshiki; Yuasa, Tomoyuki; et al. (Journal of clinical medicine, 2025)
Background: Metabolic dysfunction-associated steatotic liver disease (MASLD) causes progressive liver fibrosis. Although erythrocyte mean corpuscular volume (MCV) has been shown to have a positive correlation with all-cause mortality, the association between MCV and the development of MASLD has not been fully elucidated. Here, we examined the clinical significance of the association between MCV and MASLD. Methods: A cross-sectional study was carried out in 1009 Japanese individuals (including 186 individuals aged < 60 years and 823 individuals aged ≥ 60 years) with metabolic disorders. The relationships between MCV and noninvasive clinical markers of liver fibrosis, including fibrosis-4 (FIB-4) index, aspartate aminotransferase-to-platelet ratio index (APRI), and non-alcoholic fatty liver disease (NAFLD) fibrosis score (NFS), were statistically evaluated. Results: Using multiple and logistic regression analyses in overall subjects, it was found that MCV was positively and independently associated with the values of FIB-4 index, APRI, NFS, and the prevalence of liver fibrosis defined by each index. However, the associations between the MCV value and MASLD indices were found to be positive in subjects aged ≥ 60 years but not in those aged < 60 years. Conclusions: MCV might be a simple and useful biomarker for the development of MASLD in the elderly.